Recent advances in cancer detection using dynamic, stimuli-responsive supramolecular chemosensors. a focus review - Matsumoto, Kotaro; Nakagawa, Keiichi; Asanuma, Daisuke; Fukuhara, Gaku (Frontiers in Chemistry, 2024)
In current chemistry, supramolecular materials that respond to a wide variety of external stimuli, such as solvents, temperature, light excitation, pH, and mechanical forces (pressure, stress, strain, and tension), have attracted considerable attention; for example, we have developed cyclodextrins, cucurbiturils, pillararenes, calixarenes, crown ether-based chemical sensors, or chemosensors. These supramolecular chemosensors have potential applications in imaging, probing, and cancer detection. Recently, we focused on pressure, particularly solution-state hydrostatic pressure, from the viewpoint of cancer therapy. This Mini Review summarizes (i) why hydrostatic pressure is important, particularly in biology, and (ii) what we can do using hydrostatic pressure stimulation.